A double-potential ratiometric electrochemiluminescence platform based on g-C3N4 nanosheets (g-C3N4 NSs) and graphene quantum dots for Cu2+ detection. Issue 7 (29th January 2021) - Liu, Yiming; Sun, Yanan; Yang, Minli
Abstract : A dual-potential ratiometric ECL platform was designed for Cu 2+ detection based on the ratio of cathode signal from g-C3 N4 NSs and anode signal from GQDs. Abstract : A new kind of convenient, low-cost double-potential ratiometric ECL sensing platform for the quantification of Cu 2+ was developed with carbon nitride nanosheets (g-C3 N4 NSs) and graphene quantum dots (GQDs) as ECL luminophores. g-C3 N4 NSs mixed with multi-walled carbon nanotubes (MWCNTs) was immobilized on a glass carbon electrode (GCE) and produced strong cathodic ECL at a potential of −1.2 V ( vs. Ag/AgCl), while GQDs in the solution gave anodic ECL at +2.5 V. MWCNTs were used here to amplify the ECL signal of g-C3 N4 NSs. The addition of Cu 2+ causes the cathodic ECL signal from g-C3 N4 to decline, while the anodic ECL signal from GQDs remains unchanged. With the anodic ECL signal as an internal reference, a double-potential ratiometric ECL sensing platform for Cu 2+ was established. The ratio of the cathodic signal intensity to anodic signal intensity showed a linear response to the Cu 2+ concentration over a range from 5.0 × 10 −10 to 1.0 × 10 −6 mol L −1 and the detection limit was 0.37 nmol L −1 (3 σ / S ). Such a construction strategy alleviates the interference from the environment and therefore improves the detection accuracy of Cu 2+ . Compared with other methods for Cu 2+ detection, this method is simpler and more sensitive.